Emergence of a new opportunistic pathogen, Candida lusitaniae. - Blinkhorn, R J (1989)
Candida lusitaniae has been an infrequently reported opportunistic pathogen. Most previously reported cases of serious infection caused by this organism have proven fatal and were associated with amphotericin resistance of the organism. We report two patients with hematologic malignancies undergoing cytotoxic chemotherapy who developed fungemia with this organism while they were granulocytopenic. The organisms isolated from each patient were fully susceptible and were treated successfully with amphotericin B. When isolated from an immunocompromised host, C. lusitaniae should be considered an opportunistic pathogen and undergo antifungal susceptibility testing. Amphotericin B should be considered the drug of choice, but a poor clinical response may be indicative of a resistant isolate.